Insulin Resistance and Genetic Risk Predict Liver‐Related Outcomes and Death in Nonalcoholic Fatty Liver Disease. Issue 12 (10th October 2019) - Danford, Christopher J.; Jiang, Z. Gordon; Salomaa, Veikko; Färkkilä, Martti; Jula, Antti; Männistö, Satu; Lundqvist, Annamari; Valsta, Liisa; Perola, Markus; Åberg, Fredrik
Abstract : A pathophysiologic risk score consisting of insulin resistance and genetic risk predicts incident liver outcomes in NAFLD. Such scores may represent a viable strategy for risk stratification in NAFLD.